Custom-tailored tissue engineered polycaprolactone scaffolds for total disc replacement - Uden, S. van (2015)
Degeneration of the intervertebral disc (IVD) represents a significant musculoskeletal disease burden. Tissue Engineering has been proposing several strategies comprising the use of biodegradable materials to prepare scaffolds that can present similar mechanical properties to native IVD tissues. However, this might be insufficient, since the patientâ s intervertebral space geometry must be replicated to allow the appropriate implant fixation and integration. Herein, it is proposed the use of Reverse Engineering and Rapid Prototyping techniques applied to rabbit models aiming to prepare custom-tailored annulus fibrosus scaffolds. The IVD reverse engineered architecture was obtained by means of micro-Computed Tomography acquisition and three-dimensional modelling, resulting in a computer-aided design that replicates the original rabbit IVD. Later, a fused deposition modelling three-dimensional printer was used to produce the scaffolds with different geometries from the computer-aided design, using polycaprolactone (PCL) with 100% infill density. The microstructure of the PCL scaffolds was investigated by scanning electron microscopy (SEM), which allowed observing an adequate fusion adhesion between layers. The SEM images revealed that, until a moderate resolution, the porosities manually designed in the computer-aided design model were successfully replicated. The PCL scaffoldsâ three-dimensional architecture was also assessed by means of micro-Computed Tomography analysis. Compressive stiffness was determined using a mechanical testing system. Results showed higher values as compared to that of human IVDs (5.9-6.7 kN/mm vs. 1.2 kN/mm, respectively). In vitro studies were performed to investigate possible cytotoxicity of the polycaprolactone scaffoldsâ leachables. The results showed that the custom-tailored PCL scaffolds do not have any deleterious cytotoxic effect over annulus fibrosus cells and mouse lung fibroblasts cell line. This study proposed a simple,rapid and low-cost strategy to fabricate custom-tailored annulus fibrosus scaffolds. In the future, this strategy might be used in association with nucleus pulposus regeneration strategies that can possibly allow developing tissue engineered total disc replacement implants specific to each patient, aiming at full IVD regeneration.